UNRAVELLING IMAGE OF BOORI MA: A CASE OF SUBALTERN WOMAN IN JHUMPA LAHIRI’S A REAL DURWAN - Fortunae, Benedicta Stella (Dialectical Literature and Educational Journal, 2023)
A Real Durwan is a short story collection by Jhumpa Lahiri. The story chronicles Boori Ma, a sixty-four-year-old woman who works as Durwan, the gatekeeper and sweeper in an old building. She is a refugee from the 1947 Partition between India and Pakistan. It also portrays the condition of a woman who is ‘naturally’ considered a second-class citizen in a patriarchal society. This paper uses qualitative research method to support the analysis. Gayatri Spivak, a prominent scholar, and critic in Postcolonial studies, describes the woman as a subaltern. The subaltern refers to a person who is excluded and silenced in society. Spivak concludes that subalterns cannot speak because of repressive power and domination. Boori Ma is the portrayal of a subaltern woman. She is the main female character who experiences quadruple discrimination in relation to her gender, age, capital, and identity. Ultimately, she remains voiceless and has no choice but to leave her house due to hatred and defamation from an elite group. This paper is expected to examine four categories of discrimination: socioeconomic, ageism, gender, ethnic, and culture, and its relation to injustice towards a subaltern woman. In conclusion, it is proved that the subaltern cannot speak due to the never-ending discrimination.